Penyelesaian Masalah Transportasi dengan Degenerasi dan Siklus Berulang Menggunakan Minimum Demand Method dan Maximum Difference Extreme Difference Method - Muhtarulloh, Fahrudin; Mardiah, Evi Wardah; Huda, Arief Fatchul; Zulkarnaen, Diny (Jurusan Matematika, Fakultas Sains dan Teknologi, UIN Sunan Gunung Djati Bandung, 2023)
The transportation problem is a linear programming model that can be used to regulate distribution from a source (product supply) to a destination that requires the product optimally with minimum costs. However, when carring out optimality tests, sometimes the optimal value cannot be determined due to degeneration and repeated cycles. The aim of this research is to overcome the problem of degeneration and repeated cycles that occur in optimization problems. The methods used in this research are Minimum Demand Method (MDM) and Maximum Difference Extreme Difference Method (MDEDM) as well as the optimality test, namely Modified Distribution (MODI). The results of data analysis show that analysis show that the Minimum Demand Method has more degeneration problems, namely 132 data in the balanced case and 137 data in the unbalanced case. The Maximum Difference Extreme Difference Method has more repeated cycle problems, namely 8 data in the balanced case and 9 data in the unbalanced case. From the calculation results it can be concluded that the Maximum Difference Extreme Difference Method is more optimal than the Minimum Demand Method.